(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Upper Cretaceous Coalfield of Northern Benue Trough, represent excellent hydrocarbon source rock potential within the Nigeria inland basins. The source rock potential of coal and shale whole rock samples from Maiganga and Yaya-Ngari areas in the Northern Benue Trough was investigated using palynofacies and organic geochemical methods for hydrocarbon generation predictions. Palynofacies is integrated in this study as a useful tool for kerogen typing, paleoenvironment indicator, thermal maturity determination and hydrocarbon generation potential of source rock which equally relies on the relative abundance of the three kerogen groups (AMO, Phytoclast and palynomorphs). Current result shows that identified palynomorphs (P), phytoclast (Ph) and amorphous organic matter (AOM) for the studied Yaya-Ngari shale show significant amount of dark-brown to orange colour phytoclast compared to brown heterogenous AOM and brown to orange palynomorphs. The palynomorphs are often <10 μm, although few ones are up to 80 μm sizes. In the case of Maiganga facies, they are characterized by mainly terrestrial kerogen group. This is evidently shown by the presence of highly oxidized black, opaque tissues of higher plants often associated with some brown degraded tissue of higher plants, light brown AOM (probably resin and algae material) and trilete spore and pollens of plants. Thus, it is an indication of a more gas-prone Type III kerogen than the associated liptinitic materials of oil-prone Type II kerogen as observed under the UV-light. The GC-MS result of saturated hydrocarbon as corroborated by the aromatic hydrocarbon fraction indicates low concentration of dibenzothiophenes compared to aromatic phenanthrenes (m/z 184 and 178) which resulted in DBT/P ratio of <1. This indicates a marginal marine environment mainly deltaic setting (Maiganga) associated marine shale at Yaya-Ngari for the analysed sediments. Similarly, It is further corroborated by high concentration of hopane compared to sterane resulting in hopane/(hopane+sterane) ratio > 0.7. Generally, biomarker studies suggest deposition of Type III/II kerogen within suboxic to oxic environment for the Maiganga, while Yaya-Ngari samples are characterized by mixed organic matter deposited in a suboxic conditions.